التباين الوراثي بين بعض طرز الوردة الدمشقية (.Rosa damascena Mill) المنتشرة في مناطق مختلفة من اللاذقية بالاعتماد على مؤشر الـ RAPD. (Latakia University Journal -Biological Sciences Series, 2019)
This research was carried out to estimate the  genetic variability  btween 20 Rosa damascene genotypes dispersed in different areas of Lattakia and  to compare them with two genotypes from  Al- Marah site, to save the genetically different genotypes characterized high quality trait to be used in multiplication and for breeding and genetic improvement programs. The DNA was extracted from young leave samples followed by running (PCR-RAPD) reactions and analyzed with (12) RAPD random primers. All primers showed efficiency in estimating genetic variation between studied genotypes. Twelve primers  produced 105 fragments  in all  studied genotypes, seventy-three fragments were polymorphic. According to the  dendrogram. The genetic distance between  Lattakia genotypes and  Al-Marah genotypes was (30%) while this value reached (24%) between Lattakia genotypes. Some primers such as (FRO-11) have shown high efficiency of distinguishing between  genotypes of Lattakia and genotypes of AL- Marah.   أجري البحث لتحديد مدى التباين الوراثي بين (20) طرازاً من طرز الوردة الدمشقية Rosa damascena المنتشرة في مناطق مختلفة من اللاذقية و مقارنتها بطرازين من المراح بغية حفظ الطرز المتباينة وراثياً و ذات الصفات النوعية الجيدة للاستفادة منها سواء بإكثارها أو إدخالها في برامج التربية و التحسين الوراثي. تم استخلاص الـ DNA من النموات الورقية الحديثة، و أجري التفاعل التسلسلي للبوليميراز (PCR- RAPD) باستخدام (12 (بادئة عشوائية, أظهرت البادئات جميعها كفاءة في كشف الاختلافات الوراثية بين الطرز المدروسة. أعطت البادئات الـ (12) بالإجمال (105) حزم في كافة الطرز المدروسة حيث وصل عدد الحزم المتباينة منها عند كافة الطرز إلى (73) حزمة. بلغت نسبة التباين الوراثي بين طرز اللاذقية و طرازي المراح وفقاً لشجرة القرابة الوراثية (30%) في حين لم تتجاوز النسبة (24%) ضمن طرز اللاذقية, أظهرت بعض البادئات كالبادئة (FRO-11) كفاءة عالية في التمييز بين طرز اللاذقية و طرازي المراح.